Financial Management and QRIS Training for Traditional Market MSMEs at Sausu Trans Village - Ahmad Haekal; Sultan, Afriani; Baso Alung Gimnastiar; Ainun Zafitra; Afriani; Hasnawati A Lagaligo; Nur Intan; Nurhikma; Riska Karima (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the economy in rural areas such as Sausu Trans Village, Parigi Moutong Regency, Central Sulawesi. However, many MSME actors face challenges in financial management, such as irregular recordkeeping, mixing personal and business finances, lack of understanding of the use of Qris, lack of understanding of savings and loans and business planning. This study explores the role of financial management training as an effort to empower MSMEs through the Thematic Real Work Lecture (KKN-T) of Uin Datokarama Palu at the Traditional Market of Sausu Trans Village in collaboration with the Merah Putih Village Cooperative of Sausu Trans Village, in this activity involving the institution of Bank BRI as a presenter. In this activity, MSME actors in Sausu Trans Village were participants in the practical discussion method to improve financial literacy. The results of the evaluation showed an increase in participants’ ability to record simple finances, segregate business assets, and utilize digital financial services. This training is expected to encourage the sustainable growth of MSMEs, reduce the risk of business failure, and contribute to local economic development based on financial inclusion principles.